Veterinary practice marketeer. (24th January 2015) - Phillips, Justin
Abstract : Justin Phillips is marketing manager at White Cross Vets and the Veterinary Marketing Association's (VMA's) Young Veterinary Marketeer of the Year. Here, he describes what he does and why he believes other practices should embrace marketing to improve their quality and client care